Effects of Processing Methods and Conditioning Temperatures on the Cassava Starch Digestibility and Growth Performance of Broilers - Xuan Wang; Baolong Du; Fang Nian; Yingjun Ru; Likun Sun; Shizhen Qin; Defu Tang (Animals, 2023)
As an important food crop, cassava is rich in nutrients and high in starch content and is widely used in the production of industrial raw materials. However, the utilization value of cassava is limited due to the reduction of planting area and the existence of anti-nutritional factors. Therefore, we evaluated in vitro cassava starch digestibility and in vivo growth performance of broilers in a 3 × 3 factorial arrangement of treatments using three processing methods (mechanical crushing (MC), steam conditioning (SC), and puffing conditioning (PU)) and three conditioning temperatures (60, 75, and 90 °C) to screen for the optimal processing method and conditioning temperature to improve the utilization of cassava. In the in vitro cassava starch digestion study, the digestibility and digestion rate (p < 0.01) were higher at conditioned 90 °C than that at 60 or 75 °C, and PU was higher than SC and MC (p < 0.01) (0.25–2 h). The amylose content and amylose/amylopectin at conditioned 60 °C or PU were lower (p < 0.01) than that of 75 or 90 °C or SC, whereas the opposite was true for amylopectin content (p < 0.01). The resistant starch content of SC or PU was lower (p < 0.01) than MC. In the in vivo study, broilers fed diets conditioned at 60 °C or SC had a lower (p < 0.05) feed-to-gain ratio than those fed diets conditioned at 90 °C or PU diets. The ileum apparent digestibility of starch and AME were higher (p < 0.05) for broilers fed SC diets than for those fed MC diets. These results indicate that cassava starch promoted starch digestion rate by reducing amylose content and amylose/amylose under PU combined with a conditioning temperature of 60 °C, ileum digestibility of starch in broilers fed SC diets was higher than MC diets regardless of conditioning temperature, and SC diets increased AME and decreased F/G to promote growth performance of broilers.